(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Professional and terminology competence is an integral part of the future teacher’s professional competence. The correctness, logic, appropriateness of the use of professional terms are distinguishes a competent teacher. After all, the term is a unified international designation of a certain object, phenomenon, process and provides informative speech, adequate perception of the basic meaning. The biological terminology system include a nomenclature subsystem. A competent biology teacher in the course of his professional activity operates with both terms and nomens, which form the basis of the biological nomenclature. The purpose of the research is to identify the role and possibility of step-by-step study of terminological elements, nomens, eponyms and acronyms during the terminological professional training of a biology teacher. The main components of future biology teacher’s terminology system are indicated. The characteristic and classification of term elements, nomens, eponyms, acronyms are given. As a result of theoretical analysis and testing of the method of formation of professional and terminological competence of future biology teachers professional training it is established: 1) the effectiveness of terminological training of students is ensured by consistency and regularity; 2) the optimal stepby- step sequence of learning of biological terminology and nomenclature systems can be expressed in the form of a chain "terminoelement + nomen – acronym – eponym". An accessible, fairly simple and effective form of terminological work is the compilation of a thematic terminological dictionary, which can be presented in both handwritten and electronic form and includes short and extended definitions of terms and (or) terminological elements. One of the main tasks of future teachers terminological training is to study the semantics and etymology of terms (including eponyms and acronyms) and nomens, which are based on Latin. The formation of an active individual terminological dictionary of a student determines the further successful mastering the disciplines of professional training, understanding international scientific terminology and binary nomenclature. Mastering the complex knowledge of semantics and etymology of Greco- Latin terminoelements develops logic, enhances language culture and helps to expand the worldview of a biology student.